STUDI FENOMENOLOGIS KEBAHAGIAAN PUSTAKAWAN DALAM KEIKUTSERTAAN CALL FOR PAPER DAN CALL FOR BEST PRACTICE - Al Husna, Hana Isnaini (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2024)
(Objectives) This study aims to explore the experiences, values of happiness, and impacts of participation in the Call for Paper (CFP) and Call for Best Practice (CFBP) events organized by the Indonesian Higher Education Library Forum (FPPTI) during the 2nd International Conference of Indonesian Higher Education Libraries (KPPTI). (Method) A qualitative research approach with a phenomenological method was employed. Data were collected through interviews using open-ended questionnaires, observations, documentation, and literature reviews. The open-ended questionnaire was distributed to participants via WhatsApp groups specifically created for CFP and CFBP attendees. Data were analyzed using Interpretative Phenomenological Analysis (IPA), which involved stages such as preparing the questionnaire, taking initial notes, identifying emergent themes, formulating superordinate themes, establishing patterns across participants, and reporting findings. (Finding) The study identified five dimensions of happiness based on the PERMA framework: (a) Positive Emotions, reflected in feelings of enthusiasm, joy, pride, happiness, optimism, and satisfaction; (b) Engagement, demonstrated by the ability to submit work and present it publicly; (c) Relationships, evidenced through research collaborations; (d) Meaning and Purpose, illustrated by knowledge and experience sharing; and (e) Accomplishment and Achievement, reflected in increased publications supporting career advancements. Key benefits of participating in CFP and CFBP include enhanced writing and presentation skills, improved personal and institutional branding, sharing ideas and experiences, boosted confidence, self-actualization, expanded networking opportunities, and personal growth through breaking routines. These findings suggest that the happiness derived from such activities can enhance librarians' productivity in scientific writing and encourage continued participation in similar events with enthusiasm and positivity.